Jatropha Oil as a Substituent for Palm Oil in Biobased Polyurethane - Mohamad Ridzuan Amri; Syeed Saifulazry Osman Al-Edrus; Chuah Teong Guan; Faizah Md Yasin; Lee Seng Hua (International Journal of Polymer Science)
Polyurethanes (PUs) are unique polymers that can be tailored to suit certain applications and are increasingly used in many industrial fields. Petrochemicals are still used as the main compound to synthesize PUs. Today, environmental concerns arise in the research and technology innovations in developing PUs, especially from vegetable polyols which are having an upsurge. These are driven by the uncertainty and fluctuations of petroleum crude oil price and availability. Jatropha has become a promising substituent to palm oil so as to reduce the competition of food and nonfood in utilizing this natural resource. Apart from that, jatropha will solve the problem related to the European banning of palm oil. Herein, we review the literature on the synthesis of PUs using different vegetable oils and compare it with jatropha oil and its nanocomposites reinforced with cellulose nanocrystals. Given the potential of vegetable oil PUs in many industrial applications, we expect that they will increase commercial interest and scientific research to bring these materials to the market soon.